2011
DOI: 10.1159/000326894
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inferior Orbital Wall Morphologic Properties in Isolated Orbital Blow-Out Fracture

Abstract: Purpose: To compare inferior orbital wall morphology between isolated inferior and medial orbital wall fracture patients. Methods: The morphologic properties of patients with isolated blow-out fractures involving the medial wall or inferior wall treated from August 2004 to August 2009 were reviewed. The cross-sectional area, thickness, gradient, and curvature of the inferior wall were measured via orbital CT in the opposite non-traumatized eye. Results: Patients with isolated inferior wall fractures (n = 77) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…This theory was further studied by Song et al [8] using CT scans from a population of Korean patients with pure orbital floor or medial wall fractures. The morphologic features of the orbital floor have also been investigated by Park et al [13], who found that patients with steeper orbital floors with greater convexity were more likely to sustain isolated floor fractures than isolated medial wall fractures. Similar studies examining the ethmoidal septa and morphologic features of the orbital floor have yet to be conducted in the Japanese and Chinese populations; however, a number of general anatomic studies have been conducted on the Asian orbit.…”
Section: Discussionmentioning
confidence: 99%
“…This theory was further studied by Song et al [8] using CT scans from a population of Korean patients with pure orbital floor or medial wall fractures. The morphologic features of the orbital floor have also been investigated by Park et al [13], who found that patients with steeper orbital floors with greater convexity were more likely to sustain isolated floor fractures than isolated medial wall fractures. Similar studies examining the ethmoidal septa and morphologic features of the orbital floor have yet to be conducted in the Japanese and Chinese populations; however, a number of general anatomic studies have been conducted on the Asian orbit.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that morphologic properties, especially ethmoid air cell septa, could influence the type of blowout fracture, [11][12][13] and that the nature of the trauma could be relevant to the type of blowout fracture. In this study, ethmoid air cell septa and etiology of injury were analyzed with regard to fracture type.…”
mentioning
confidence: 99%
“…A computer-assisted rapid prototyping technique assisted in performing www.nature.com/scientificreports/ precise surgical procedures and anticipating the contour of recipient sites. Park et al 27 presented the anatomical characteristics of patients with orbital wall fracture. Orbital CT images were analyzed according to the area and thickness of the orbital wall and the coefficient of curvature.…”
Section: Discussionmentioning
confidence: 99%